The Debate on the Aesthetics of Business Brand Innovation Among the Millennial Generation for the Issuance of Halal Certification - Haryati, Haryati; Junaidi, Heri; Mohammed Rateb, Sheikh (Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study explores how millennials debate culinary businesses, focusing on consumer tastes, brand aesthetics, and halal certification. The basic assumption is that the “halal logo” for the community is not a standard for the business. The method used in this study uses the library research method. The main issues in the study of food business issues to obtain halal certification and the issue of debate among the millennial generation. Stages in data collection techniques are Inventory, Critical Evaluation and Synthesis. The data that has been collected is analyzed descriptively by general data to specific data so as to find conclusions that can become recommendations. The study found that while branding isn't part of the halal assessment, it strongly connects to Indonesia's majority Muslim community. Although including halal products, the basic ingredients of these products are not easy to produce at will. When halal food is stored in one place with haram food, it will cause the food to be contaminated, such as chicken stored in the same place as pork. From the same side, the obligation of halal certification is carried out as a form of state effort in providing security for its citizens in consuming food. Between the two understandings, literacy is needed for the millennial generation where certification and labeling of halal products based on protection, fair value, definite legal value, responsibility and openness, effective and efficient, and competent have implications for public comfort in consuming food for food that is proven to be halal. Millennials are becoming aware that brands with elements seen as forbidden can face public scrutiny, impacting their products. This often leads to short-lived success, with businesses fading away and ultimately financial loss.